Expanding Coercive Mobility Theory: Women's Forms of Capital and Neighborhood Social Control - Cwick, Jaclyn Marie (2016)
This dissertation proposes a gendered theory of coercive mobility, synthesized from the collateral consequences of incarceration, along with coercive mobility theory and literature on forms of capital. Previous work has shown that the removal of residents due to mass incarceration contributes to disruptions in neighboring relationships and therefore, impedes the community’s ability to prevent crime, commonly referred to as informal social control. This involuntary mobility due to prison admissions and returns, known as coercive mobility, has focused almost entirely on the collateral consequences to the incarcerated, a predominantly male population. However, those who remain in the community, primarily women, also experience disruptions to their neighboring relationships. This disruption leads to reductions in women’s capital due to the incarceration of concentrated segments of male residents, including a reduction in social capital (e.g., resources that lie within these neighboring relationships), physical capital (e.g., income), and human capital (e.g., education). Therefore, women’s capital is incorporated as a mechanism to more fully explain the process by which concentrated incarceration unfolds and results in reductions in neighborhood social control. In addition to incorporating women’s capital as a mechanism in the relationship between incarceration and informal social control, the proposed theory fills an evident gap in the literature by examining the consequences of incarceration for female residents, as well as the gendered or differential effects of incarceration to women and men. Using data on Baltimore residents, the dissertation tests the proposed theory by estimating the association between incarceration (prison admissions and releases) and women’s and men’s capital and social control at the neighborhood-level with the use of ordinary least squares regression models, and at the individual-level, while controlling for neighborhood characteristics, using hierarchical linear modeling. Furthermore, women’s and men’s capital are tested as mediators in the relationship between incarceration and social control at both levels. Findings provide support for a gendered theory of coercive mobility, advancing our understanding of the community consequences of incarceration to female residents, and offer suggestions for future research and policy implications